Assessment and Health Service Quality Improvement Plan - Edna Fauziah S (International Journal of Science and Society, 2023)
Many Puskesmas in Indonesia have health service problems, such as a lack of health facilities and the availability and quality of health workers at Puskesmas. This study aims to examine the quality of health services and strategies for improving them in Indonesia. They were using a literature review process. The number of articles studied by the database: Google Scholar with 22 articles, Pubmed, PMC, and Proquest with 1 article each. The results of the study are (1) Quality of health services at the Indonesian Health Centers, consisting of direct evidence; reliability; responsiveness; guarantee; and empathy have been successfully carried out by many puskesmas in Indonesia, such as Sangura Health Center, Ibun Health Center, Mangasa Health Center, and Sumedang District Health Center and (2) Plans to increase the quality of Health Center health services in Indonesia in terms of health human resources, namely by taking training and education, using Health workers in a fair, coordinated and balanced manner as well as delivery of benefits, preparation of resources and support services.